ANALISIS KEMAMPUAN KOMUNIKASI SISWA DALAM MENYELESAIKAN SOAL POLA BILANGAN - Qomalhaq, Shenlie Wilanda; Falak, Agam Fajrul (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Research conducted to find out the level of communication skills of students, in the point of the number pattern that contains 5 points of essay problems. The instrument has passed the problem validation test and was tested to students of grade VIII of one of the State Junior High Schools in West Bandung Regency, by conducting the following process: 1). Preparation, 2). Implementation and 3). Evaluation. This research uses a derifrift method with data collection techniques through observations. Data obtained from the results of instrument trials and the results of errors in the settlement process, and the results of the study showed that students' communication skills were at moderate interpretation.